Application of Problem-Based Learning in Business Mathematics - Subakti, Jani; Wibowo, Agung; Hanifan , M. Zakie (INOVATOR, 2025)
Problem-based learning (PBL) is an innovative approach that can improve students' problem-solving and critical thinking skills. In the context of Business Mathematics, PBL offers a way to connect mathematical theory with real-world applications relevant to the business world. This study aims to explore the application of problem-based learning in Business Mathematics courses and analyze its impact on students' conceptual understanding and problem-solving abilities. The results show that PBL can improve students' learning motivation and understanding of mathematical concepts often considered difficult, such as financial analysis, interest calculation, and optimization. This study also provides recommendations for the development of problem-based learning methods in Business Mathematics education